Oscillation of Second Order nonlinear Neutral Difference Equations - S. Sindhuja, J. Daphy Louis Lovenia, A. P. Lavanya (Mathematical Statistician and Engineering Applications, 2022)
In this paper, we study the oscillatory behavior of secondorder nonlinear neutraldifference equation of the form Examples are provided to illustrate the results.